A multilevel longitudinal study of adolescent Internet addiction: The role of obsessive–compulsive symptoms and classroom openness to experience. Issue 1 (2nd January 2016) - Stavropoulos, Vasilis; Gentile, Douglas; Motti-Stefanidi, Frosso
Abstract : Internet addiction (IA) in adolescence was longitudinally examined in relation to individual obsessive–compulsive symptoms and the personality trait of openness to experience (OTE) at the classroom level. The study consists of a two-point measure of a normative sample comprising 648 Greek adolescents (retention = 363, age 16–18 years, wave 1: age = 15.75 years, SD = 0.57, males = 46.2%, females = 53.8%). IA was assessed with the IA Test (Young, K. S. [1998]. Caught in the net: How to recognize the signs of internet addiction—And a winning strategy for recovery . New York, NY: Wiley), obsessive–compulsive symptoms with the Symptom check list 90 revised (Derogatis, L. R., & Savitz, K. L. [1999]. The SCL-90-R, brief symptom inventory, and matching clinical rating scales. In M. E. Maruish (Ed.), The use of psychological testing for treatment planning and outcomes assessment (2nd ed., pp. 679–724). Mahwah, NJ: Lawrence Erlbaum Associates Publishers) and OTE with the FFFK (Asendorpf, J. D., & van Aken, M. A. G. [2003]. Validity of big five personality judgments in childhood: A 9 year longitudinal study. European Journal of Personality, 17, 1–17). A three-level hierarchical linear model investigated individual- and classroom-level effects on IA score and its changes over time. The findings revealed that IA at the initial level was associated with the obsessive–compulsive symptoms of the individual and negatively related to classroom-level OTE. However, adolescents high on obsessive–compulsive symptoms in high on OTE classrooms presented higher IA scores over time.